Development and characterization of 35 single nucleotide polymorphism markers for the brown alga Fucus vesiculosus - Cánovas, Fernando G. (2012)
We characterized 35 single nucleotide polymorphism (SNP) markers for the brown alga Fucus vesiculosus. Based on existing Fucus Expressed Sequence Tag libraries for heat and desiccation-stressed tissue, SNPs were developed and confirmed by re-sequencing cDNA from a diverse panel of individuals. SNP loci were genotyped using the SEQUENOM single base extension iPLEXTM system for multiplex assays on the MassARRAY platform, which uses matrix-assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF MS) to discriminate allele-specific products. The SNP markers showed a wide range of variability among 16 populations from the south-west of the UK, northern Portugal and Morocco. The analysis of the information provided by these markers will be useful for studying population structure, historical demography and phylogeography of F. vesiculosus. They can also be used for the identification of genes and/or linked genomic regions potentially subject to selection in response to abiotic stressors like temperature extremes and desiccation intensity that vary across habitats and geographical range.